Cable inspection unmanned aerial vehicle based on grid planning - SUN XIAOWEI; ZHANG HONGYAN; GONG ZHENGGUO; YAN QI; WEI QIUHUI; ZHANG XINGSHI; ZHAO ZHAN; WANG BAIBING; YANG PENG; FENG YUAN; ZHANG XI; MA JIANBO (2025)
The invention discloses a grid planning-based cable inspection unmanned aerial vehicle which comprises an unmanned aerial vehicle body, a driving mechanism is arranged on the lower surface of the unmanned aerial vehicle body, a driving motor is arranged on one side of the driving mechanism, a counterweight device is arranged at the lower end of the driving mechanism, and driving fans are arranged on the two sides of the unmanned aerial vehicle body. A detection device is arranged on the lower surface of the unmanned aerial vehicle body, and an auxiliary power device is arranged in the unmanned aerial vehicle body. The counterweight device can be driven by the driving mechanism to move downwards, and the supporting wheels make contact with a cable needing to be detected. And meanwhile, the counterweight battery below the linkage rod can move downwards, so that the gravity center of the unmanned aerial vehicle body is lowered to be lower than the height of the cable, and the effect of stabilizing the unmanned a